Analysis Of Human Resource Competency On Islamic Boarding School To Financial Management Islamic Boarding School In West Java - Ira Siti Rohmah Maulida; Arif Rijal Anshori; Neng Dewi Himayasari; Ifa Hanifia Senjiati (Journal of Islamic Business and Economic Review, 2020)
Employment and finance are two aspects that must be considered and need to be repaired in the management of schools. In Reality, management of Islamic Boarding Schools still use simple management, that caused due to the limited quality the power of man-manager boarding. The formulation of the problem in this research is 1) How is the financial management of Islamic boarding schools in West Java ?. 2) How does the analysis of the competence of the manager of finance boarding against management finance boarding schools in Java West?The method of research used  research qualitative with approach descriptive. Data collection techniques were carried out by giving questionnaires to representatives of 14 Islamic Boarding School in West Java. Analysis of data using analysis of narrative is based on findings that there is.The results of the discussion of the research: 1) The majority of schools or 92.9% already manage finances with the good , and 7.1% of schools are not managing finances with good. 2) Pondok Islamic Boarding School, who already has human resourches competency that good and not suitable, can be seen on the appropriateness of expenses or do not exceed the budget.